Transformasi Profesionalisme Guru di Era Disrupsi: Tinjauan Kritis terhadap Kebijakan Pendidikan Digital - AULIA, RIDHA; B.Fernandez, Reyneldis; Yuliana, Gina; Aribah, Lutfina; Watia, Larasi (CV. Master Literasi Indonesia, 2026)
Digital education transformation is often misinterpreted as limited to the provision of infrastructure and bureaucratic digitalization, which ironically burdens educators. This article aims to critically analyze the synergy between digital education policy and the transformation of teacher professionalism in the era of disruption. Using the library study method with a qualitative content analysis approach, this study dissects the picture between the regulatory text and the reality in the field. The results of the study show three main findings. First, teachers are required to evolve from mere application operators to digital learning designers. Second, regulations centered on the provision of application administration have triggered the pressure of technology and performative work culture, thereby eroding the fundamental essence of teaching activities. Third, a reorientation towards adaptive and humanist policies is needed. At the macro level, the government needs to debureaucratize through integrated data integration, while at the micro level, school leadership must be present as a protective shield that ensures the psychological well-being of teachers. In conclusion, policy synergy that favors the welfare of educators is an absolute prerequisite for technology to function as an instrument of empowerment, not a rigid supervisory tool that shuts down pedagogical innovation.